Electrolyte and lithium ion battery

By combining isoxazole compounds and fluorocarboxylate compounds in the lithium-ion battery electrolyte, the problem of difficult to take into account the kinetic performance and thermal stability of the existing electrolyte is solved, and the effect of improving the fast charging performance of lithium-ion batteries and taking into account the high-temperature stability of high-temperature.

CN119650843AActive Publication Date: 2025-03-18ZHUHAI COSMX BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411872422.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The dynamic performance and thermal stability of existing lithium-ion battery electrolytes are difficult to take into account, which leads to the need to improve the fast charging performance of lithium-ion batteries.

Method used

An electrolyte containing isoxazole compounds and fluorocarboxylic acid ester compounds is used, and the mass percentage of isoxazole compounds is between 3% and 20% and the mass percentage of fluorocarboxylic acid ester compounds is between 5% and 40%. The kinetic performance and high temperature stability of the electrolyte are improved by combining these compounds.

Benefits of technology

The electrolyte can broaden the charging window of lithium-ion batteries, improve the fast charging capability of lithium-ion batteries, and at the same time it has high temperature stability, improving the low-temperature performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196078920000021
    Figure BDA0005196078920000021
  • Figure BDA0005196078920000031
    Figure BDA0005196078920000031
  • Figure BDA0005196078920000041
    Figure BDA0005196078920000041
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to an electrolyte and a lithium ion battery. The electrolyte comprises an isoxazole compound and a fluoro-carboxylic ester compound, and based on the total mass of the electrolyte, the mass percentage content A% of the isoxazole compound is 3%-20%, and the mass percentage content B% of the fluoro-carboxylic ester compound is 5%-40%. According to the present invention, the specific amount of the isoxazole compound and the fluorocarboxylic acid ester compound are combined and used in the electrolyte, such that the electrolyte has good dynamic performance and good high-temperature stability so as to broaden the charging window of the lithium ion battery, improve the rapid charging capacity of the lithium ion battery, and simultaneously provide the high-temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an electrolyte and a lithium-ion battery. Background Art

[0002] The wide application of lithium-ion batteries in 3C electronics, energy storage, new energy vehicles and other industries has brought great convenience to people's daily lives. At present, both consumer electronics batteries and power batteries hope that the charging time of lithium-ion batteries can be faster to improve the experience of terminal products.

[0003] Positive electrode materials, negative electrode materials, separators and electrolytes are the four main components of conventional lithium-ion batteries, and they all play a vital role in the fast charging performance of the battery. In particular, the electrolyte components are greatly affected by temperature, solubility, melting point, boiling point and viscosity, and the kinetic performance of electrolytes with different formulations varies greatly. In addition, the development demand for lightweight lithium-ion batteries has made the thickness of lithium-ion battery poles and the compaction density of materials more stringent, further putting forward higher requirements on the kinetic performance of lithium-ion batteries.

[0004] At present, conventional carbonate and carboxylate-based electrolytes have limited kinetic properties. In order to enable lithium-ion batteries to meet the requirements of cycling and safety, some solvents and additives with poor thermodynamic stability have become necessary components, further limiting the improvement of the kinetic properties of lithium-ion electrolytes.

[0005] In order to break through the current limitations of the kinetic performance of lithium-ion battery electrolytes, it is urgent to develop lithium-ion battery electrolytes with better kinetic performance and high-temperature stability to broaden the charging window of lithium-ion batteries and improve the fast charging capability of lithium-ion batteries. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present application is to overcome the defects in the prior art that the kinetic performance and thermal stability of the lithium-ion battery electrolyte cannot be taken into account at the same time, and the fast charging performance of the lithium-ion battery needs to be further improved, so as to provide an electrolyte and a lithium-ion battery.

[0007] To this end, this application provides the following technical solutions:

[0008] According to one aspect of the present application, an electrolyte is provided, comprising: an isoxazole compound and a fluorocarboxylate compound. Based on the total mass of the electrolyte, the mass percentage A% of the isoxazole compound is 3%-20%, and the mass percentage B% of the fluorocarboxylate compound is 5%-40%.

[0009] In some preferred embodiments, the mass percentage A% of the isoxazole compound and the mass percentage B% of the fluorocarboxylate compound satisfy the following relationship:

[0010] 15≤A+B≤50, and 0.5≤B / A≤10.

[0011] In some preferred embodiments, the isoxazole compound has the following structure:

[0012]

[0013] Wherein, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, alkyl, alkoxy, haloalkyl, haloalkoxy, alkylamino, and haloalkylamino;

[0014] Preferably, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, C1-C2 alkyl, C1-C2 alkoxy, C1-C2 haloalkyl, C1-C2 haloalkoxy, C1-C2 alkylamino, and C1-C2 haloalkylamino;

[0015] Further preferably, the isoxazole compound has any of the following structures:

[0016]

[0017] More preferably, the isoxazole compound is a fluorine-containing isoxazole compound.

[0018] In some optional embodiments, the fluorocarboxylic acid ester compound includes at least one of ethyl fluoroacetate, propyl fluoroacetate, methyl fluoropropionate, ethyl fluoropropionate, methyl fluoroacetate, propyl fluoropropionate, isopropyl fluoropropionate, isopropyl fluoroacetate, ethyl fluorobutyrate, ethyl fluoroisobutyrate, methyl fluoroisobutyrate, butyl fluoroacetate, isobutyl fluoroacetate, and tert-butyl fluoroacetate;

[0019] Preferably, the fluorocarboxylate compound has any of the following structures:

[0020]

[0021] In some optional embodiments, a carbonate solvent is also included;

[0022] Preferably, based on the total mass of the electrolyte, the mass percentage of the carbonate solvent is 15%-45%.

[0023] In some optional embodiments, a lithium salt is further included, wherein the lithium salt includes LiPF6 and a sulfonic acid lithium salt;

[0024] Preferably, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 8%-18%; the mass percentage of the sulfonic acid lithium salt is 3%-12%;

[0025] More preferably, the total addition amount L% of the lithium salt is 16%-26%.

[0026] In some optional embodiments, sulfur-containing additives and / or nitrile compounds are also included;

[0027] Preferably, based on the total mass of the electrolyte, the mass percentage S% of the sulfur-containing additive is 1%-5%;

[0028] Further preferably, the mass percentage S% of the sulfur-containing additive and the mass percentage A% of the isoxazole compound satisfy the following relationship:

[0029] 1≤A / S≤10;

[0030] Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, vinyl bissulfate, methylene disulfonate, trimethylsilyl methane sulfonate, dimethyl methylene sulfonate, 4-acetylphenyl trifluoromethane sulfonate, phenyl trifluoromethane sulfonate, and 6-quinolyl trifluoromethane sulfonate;

[0031] Preferably, the nitrile compound includes at least one of benzonitrile, p-toluene nitrile, 3,5-difluorobenzonitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, and 1,2,3-tris(2-cyano)propane.

[0032] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.

[0033] In some optional embodiments, the invention further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the compaction density of the negative electrode active material is 1.65-1.80 g / cm 3 , the porosity of the negative electrode sheet ranges from 10% to 45%.

[0034] In some optional embodiments, a recessed area is provided on the negative electrode active material layer, and the width of the recessed area is 50 μm-200 μm;

[0035] Preferably, the depth of the recessed area is 3 μm-45 μm.

[0036] The technical solution of this application has the following advantages:

[0037] The electrolyte provided by the present application includes: an isoxazole compound and a fluorocarboxylate compound. Based on the total mass of the electrolyte, the mass percentage A% of the isoxazole compound is 3%-20%, and the mass percentage B% of the fluorocarboxylate compound is 5%-40%. The present application combines a specific amount of isoxazole compounds and fluorocarboxylate compounds in the electrolyte, so that the electrolyte has both good kinetic performance and high temperature stability, thereby broadening the charging window of the lithium-ion battery, improving the fast charging capability of the lithium-ion battery, and having high temperature stability. Specifically, isoxazole compounds are miscible with conventional electrolyte components, and isoxazole compounds have a low melting point and low viscosity, which can reduce the viscosity of the electrolyte, improve the conductivity and wettability, and thus improve the fast charging capability of lithium-ion batteries, broaden the charging window of lithium-ion batteries, and also improve the low-temperature performance of lithium-ion batteries; fluorocarboxylate compounds have good antioxidant properties, high-temperature stability and a moderate dielectric constant, and fluorocarboxylate compounds can inhibit the oxidative decomposition of isoxazole compounds at the positive electrode, while improving the thermal stability of the electrolyte. However, due to the high viscosity of fluorocarboxylate compounds, their use in combination with isoxazole compounds can reduce the viscosity of the electrolyte while giving the electrolyte good kinetic properties and high-temperature stability. Therefore, the combined use of the two can broaden the charging window of lithium-ion batteries, improve the fast charging capability of lithium-ion batteries, and have high-temperature stability.

[0038] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. DETAILED DESCRIPTION

[0039] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0041] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0042] According to one aspect of the present application, an electrolyte is provided, comprising: an isoxazole compound and a fluorocarboxylate compound. Based on the total mass of the electrolyte, the mass percentage A% of the isoxazole compound is 3%-20%, and the mass percentage B% of the fluorocarboxylate compound is 5%-40%.

[0043] As an example, based on the total mass of the electrolyte, the mass percentage A% of the isoxazole compound is 3%, 5%, 8%, 10%, 12%, 15%, 17%, 19%, 20%, or within the range of any of the above values; the mass percentage B% of the fluorocarboxylic acid ester compound is 5%, 8%, 10%, 12%, 15%, 17%, 19%, 20%, 23%, 25%, 28%, 30%, 35%, 40%, or within the range of any of the above values.

[0044] The present application can make the battery have both good fast charging capability and high temperature stability by combining a specific amount of isoxazole compounds and fluorocarboxylic acid ester compounds in the electrolyte. Specifically, isoxazole compounds can be soluble in conventional electrolyte components, and isoxazole compounds have a low melting point and low viscosity, which can reduce the viscosity of the electrolyte, improve the conductivity and wettability, and thus improve the fast charging capability of lithium-ion batteries, broaden the charging window of lithium-ion batteries, and improve the low temperature performance of lithium-ion batteries; fluorocarboxylic acid ester compounds have good antioxidant properties, high temperature stability and moderate dielectric constants, and fluorocarboxylic acid ester compounds can inhibit the oxidation and decomposition of isoxazole compounds at the positive electrode, while improving the thermal stability of the electrolyte, but due to the large viscosity of fluorocarboxylic acid ester compounds, the use of isoxazole compounds can reduce the viscosity of the electrolyte while making the electrolyte have good kinetic properties, therefore, the combined use of the two can broaden the charging window of lithium-ion batteries, improve the fast charging capability of lithium-ion batteries, and have high temperature stability. If the amount of isoxazole compounds added is too small, the battery performance will hardly be improved due to the small effect on the viscosity and conductivity of the electrolyte; if the amount is too large, the high temperature performance and cycle stability of the battery will be poor due to the fact that the anti-oxidation and reduction stability and high temperature stability of isoxazole compounds are not as good as those of conventional carbonate and carboxylic acid ester solvents. If the amount of fluorocarboxylic acid ester compounds added is small, their amount cannot inhibit the continuous oxidative decomposition of isoxazole compounds at the positive electrode; if the amount is too large, the viscosity of the electrolyte is too high, which is not conducive to the fast charging performance of lithium-ion batteries.

[0045] In some optional embodiments, the mass percentage A% of the isoxazole compound and the mass percentage B% of the fluorocarboxylate compound satisfy the following relationship:

[0046] 15≤A+B≤50, and 0.5≤B / A≤10.

[0047] As an example, the value of A+B can be 15, 18, 20, 23, 28, 30, 34, 37, 40, 45, 50, or a range thereof; the value of B / A can be 0.5, 1, 3, 5, 7, 9, 10, or a range thereof.

[0048] In the present application, the dosage relationship of the isoxazole compound and the carboxylate compound is within the above-mentioned appropriate range, and the electrolyte can obtain a lower viscosity and good conductivity and electrode wettability, so that the lithium-ion battery has a better fast lithium charging window, a wider electrochemical window and better cycle stability.

[0049] In some optional embodiments, the isoxazole compound has the following structure:

[0050]

[0051] Wherein, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, alkyl, alkoxy, haloalkyl, haloalkoxy, alkylamino, and haloalkylamino;

[0052] Preferably, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, C1-C2 alkyl, C1-C2 alkoxy, C1-C2 haloalkyl, C1-C2 haloalkoxy, C1-C2 alkylamino, and C1-C2 haloalkylamino;

[0053] Further preferably, the isoxazole compound has any of the following structures:

[0054]

[0055] More preferably, the isoxazole compound is a fluorine-containing isoxazole compound.

[0056] In the present application, the fluorine-containing isoxazole compound has better antioxidant stability and can be adapted to higher voltage lithium-ion batteries. For example, it can circulate normally in a lithium-ion battery with a charging upper limit voltage of 4.2V-4.53V.

[0057] In some optional embodiments, the fluorocarboxylic acid ester compound includes at least one of ethyl fluoroacetate, propyl fluoroacetate, methyl fluoropropionate, ethyl fluoropropionate, methyl fluoroacetate, propyl fluoropropionate, isopropyl fluoropropionate, isopropyl fluoroacetate, ethyl fluorobutyrate, ethyl fluoroisobutyrate, methyl fluoroisobutyrate, butyl fluoroacetate, isobutyl fluoroacetate, and tert-butyl fluoroacetate;

[0058] Preferably, the fluorocarboxylate compound has any of the following structures:

[0059]

[0060] In some optional embodiments, a carbonate solvent is also included;

[0061] Preferably, based on the total mass of the electrolyte, the mass percentage of the carbonate solvent is 15%-45%.

[0062] In the present application, the carbonate solvent includes a fluorinated carbonate solvent, and the fluorinated carbonate solvent includes but is not limited to at least one of fluorinated ethylene carbonate, fluorinated propylene carbonate, fluorinated methyl ethyl carbonate, fluorinated diethyl carbonate, etc. Carbonate solvents have a high dielectric constant, and adding an appropriate amount in the electrolyte can promote the dissolution of lithium salts; fluorinated carbonates have good resistance to electrochemical oxidation, and adding an appropriate amount in the electrolyte can improve the overall antioxidant performance of the electrolyte and improve the high-voltage cycle stability of the battery. After adding an appropriate amount of carbonate solvents and isoxazole compounds to the electrolyte at the same time, the carbonate solvents that are easy to form a film preferably form a film at the negative electrode, blocking the direct contact between the isoxazole compounds and the negative electrode, and improving the anti-reduction stability of the isoxazole compounds. In addition, in the electrolyte, carbonate solvents with high dielectric constants occupy the first solvent sheath of lithium ions, and isoxazole compounds with good kinetic properties surround the first solvent sheath, reducing the viscosity of the electrolyte and facilitating the rapid transmission of lithium ions in the electrolyte. The combined use of carbonate solvents and isoxazole compounds can improve the anti-oxidation and reduction stability of the electrolyte, while taking into account good conductivity and fast charge and discharge capabilities.

[0063] In some optional embodiments, a lithium salt is further included, wherein the lithium salt includes LiPF6 and a sulfonic acid lithium salt;

[0064] In the present application, the sulfonic acid lithium salt refers to the lithium salt having a sulfonic acid structure in its anionic structure. Typically, the sulfonic acid lithium salt mainly includes but is not limited to: lithium bis(trifluoromethylsulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyllithium, etc.

[0065] LiPF6 is the most commercially used electrolyte at present. It has suitable electrical conductivity and can passivate aluminum foil. However, in the face of increasingly high fast charging requirements, due to the small volume of the hexafluorophosphate in LiPF6 and the insufficient dissociation degree of positive and negative ions, pure LiPF6 is difficult to meet the kinetic requirements. To this end, further optimization is needed on lithium salts and solvents to improve the kinetic properties of lithium-ion electrolytes. Sulfonic acid lithium salts generally have a larger anion structure, and the negative charge density on the anion is low and is easily dissociated. Therefore, sulfonic acid lithium salts generally have a higher ion migration number. The combined use of sulfonic acid lithium salts and LiPF6 can further improve the fast charging capability of lithium-ion electrolytes to a certain extent.

[0066] Preferably, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 8%-18%; the mass percentage of the sulfonic acid lithium salt is 3%-12%;

[0067] Further optionally, the total addition amount L% of the lithium salt is 16%-26%;

[0068] As an example, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 8%, 10%, 12%, 15%, 18%, or within the range of any of the above values; the mass percentage of the sulfonic acid lithium salt is 3%, 5%, 7%, 9%, 10%, 12%, or within the range of any of the above values; the total addition amount of the lithium salt is 16%, 18%, 20%, 22%, 24%, 26%, or within the range of any of the above values.

[0069] In the present application, a higher lithium salt concentration can make the electrolyte maintain good electrochemical stability and good fast charging performance. When isoxazole compounds are used in the electrolyte, since isoxazole compounds have a lower viscosity, the addition of an appropriate amount of isoxazole compounds can reduce the viscosity of the electrolyte, so that the electrolyte with a higher lithium salt content maintains good kinetic properties. In addition, since the -ON- structure on the isoxazole structure gives isoxazole compounds a certain ability to attract lithium ions, the application of isoxazole compounds can further promote the degree of dissociation of sulfonic acid lithium salts and improve the fast charging performance of lithium ion electrolytes. The combination of isoxazole compounds and mixed lithium salts of appropriate concentrations can make the electrolyte have good antioxidant stability and kinetics, which is beneficial for lithium-ion batteries to have a wider charging window and faster charging and discharging capabilities.

[0070] More preferably, the total addition amount L% of the lithium salt and the mass percentage content A% of the isoxazole compound satisfy the following relationship:

[0071] 1≤L / A≤8.

[0072] As an example, the value of L / A may be 1, 3, 5, 7, 8, or any range thereof.

[0073] When the lithium salt concentration is high and the amount of isoxazole solvent added is low, the viscosity of the electrolyte is too high, which will deteriorate the fast charging performance of lithium ions; when the lithium salt concentration is low and the amount of isoxazole solvent added is high, the stability of the electrolyte becomes poor due to too many free isoxazole solvent molecules, which easily leads to its decomposition and gas production at the positive electrode. L / A in the appropriate range can make the electrolyte have both good antioxidant stability and kinetic performance.

[0074] In some optional embodiments, sulfur-containing additives and / or nitrile compounds are also included;

[0075] In the present application, in order to block the direct contact between the isoxazole compound and the positive and negative electrode active materials and improve the anti-oxidation and reduction stability of the isoxazole compound, an appropriate amount of sulfur-containing additive can be added to the electrolyte, and the sulfur-containing additive can form a film on the surface of the positive and negative electrode active materials, and reduce the redox decomposition of the components with poor anti-oxidation and reduction properties in the electrolyte. Typically, the sulfur-containing additive includes but is not limited to 1,3-propane sultone (PS), 1,3-propylene sultone (PST), vinyl sulfate (DTD), divinyl sulfate (BiDTD), methylene disulfonate (MMDS), trimethylsilyl methane sulfonate, dimethyl methylene sulfonate, 4-acetylphenyl trifluoromethane sulfonate, phenyl trifluoromethane sulfonate, 6-quinolyl trifluoromethane sulfonate. One or more. The nitrile compound includes but is not limited to at least one of benzonitrile, p-toluenenitrile, 3,5-difluorobenzonitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, and 1,2,3-tris(2-cyano)propane.

[0076] In addition, in order to further improve the antioxidant stability of isoxazole compounds, an appropriate amount of nitrile compounds can be added to the electrolyte. Since nitrile compounds are preferably adsorbed on the surface of the positive electrode active material, after the isoxazole compounds carry lithium ions and migrate to the surface of the positive electrode active material, they will be physically hindered by the nitrile substances, so that the isoxazole compounds and lithium ions are separated in advance, avoiding direct contact between the isoxazole compound molecules and the positive electrode active material. Therefore, the combination of isoxazole compounds and positive electrode protection additives can make the electrolyte have good kinetic properties and antioxidant stability at the same time, and inhibit the oxidation gas production side reaction of lithium-ion batteries.

[0077] Preferably, based on the total mass of the electrolyte, the mass percentage S% of the sulfur-containing additive is 1%-5%; as an example, the mass percentage of the sulfur-containing additive is 1%, 2%, 3%, 3.5%, 4%, 5%, or within the range of any of the above values.

[0078] Preferably, based on the total mass of the electrolyte, the mass percentage of the nitrile compound is 1%-5%; as an example, the mass percentage of the nitrile compound is 1%, 2%, 3%, 3.5%, 4%, 5%, or within the range of any of the above values.

[0079] Further preferably, the mass percentage S% of the sulfur-containing additive and the mass percentage A% of the isoxazole compound satisfy the following relationship:

[0080] 1≤A / S≤10.

[0081] As an example, the ratio of A / S can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or within the range of any of the above values. In the present application, when the amount of isoxazole compound added is too much and the amount of sulfur-containing additive added is too little, the sulfur-containing additive cannot effectively inhibit the high-temperature gas production of the isoxazole compound, and the high-temperature performance of the battery is poor; when the amount of isoxazole compound added is low and the amount of sulfur-containing additive added is high, the dynamics of the battery deteriorates, and although the high-temperature storage performance is excellent, the battery charging window and cycle performance deteriorate.

[0082] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.

[0083] In some optional embodiments, the invention further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the compaction density of the negative electrode active material is 1.65-1.80 g / cm 3 , the porosity of the negative electrode sheet ranges from 10% to 45%;

[0084] In some optional embodiments, the present invention further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the compaction density of the positive electrode active material is 4.0-4.3 g / cm 3 , the porosity of the positive electrode sheet ranges from 15% to 35%.

[0085] As an example, the compaction density of the negative electrode active material is 1.65 g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.80g / cm 3, or within the range of any of the above values; the porosity of the negative electrode sheet is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or within the range of any of the above values; the compaction density of the positive electrode active material is 4.0g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.25g / cm 3 , 4.3g / cm 3 , or within the range formed by any of the above values; the porosity of the positive electrode sheet is 15%, 20%, 25%, 30%, 35%, or within the range formed by any of the above values.

[0086] Those skilled in the art can understand that if the compaction density of the active material is too low and the porosity of the pole piece is too high, the energy density of the battery is small and the conductivity of the pole piece deteriorates, the electrochemical impedance will increase and the kinetic performance of the battery will deteriorate; if the compaction density of the active material is too high and the porosity of the pole piece is too low, the transmission of lithium ions will be more difficult, which may easily lead to poor lithium deposition or insertion of the battery.

[0087] In some optional embodiments, a recessed area is provided on the negative electrode active material layer, and the width of the recessed area is 50 μm-200 μm; as an example, the width of the recessed area is 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 170 μm, 200 μm, or within a range consisting of any of the above values;

[0088] Preferably, the depth of the recessed area is 3 μm-45 μm. As an example, the depth of the recessed area is 3 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or within a range consisting of any of the above values.

[0089] In some optional embodiments, the recessed area is prepared by laser scribing;

[0090] In some optional implementations, the positive electrode sheet and / or the negative electrode sheet is punched; the punching is optionally performed using a laser.

[0091] In the present application, the electrode material has a higher compaction density, which can make the energy density of the battery higher, but the high compaction density will cause the wettability of the electrolyte and the liquid retention of the battery to deteriorate, thereby deteriorating the interface of the electrode and causing the cycle life of the battery to deteriorate. Although adding isoxazole compounds to the electrolyte can enhance the wettability of the electrolyte and improve the fast charging performance of the battery. However, when the compaction density of the electrode material is higher, the gaps between the electrode materials become less, the infiltration of the electrolyte becomes worse, the migration of lithium ions in the electrode slows down, and the lithium ion replenishment rate in the electrolyte also slows down. Therefore, only improving the dynamics of lithium ion electrolytes cannot effectively solve the problem of poor charge and discharge dynamics of high compaction density lithium ion batteries. For this reason, laser scribing and / or laser drilling can be performed on the negative electrode sheet. On the one hand, laser scribing or drilling shortens the migration path of lithium ions to the bottom of the pole piece, and on the other hand, the space formed by scribing or drilling can promote the infiltration of the electrolyte and store the electrolyte, reducing the risk of capacity diving due to lack of liquid in the late cycle of lithium ion batteries. In addition, in order to further improve the dynamics of lithium-ion batteries, holes can be punched on the positive electrode sheet, which is also beneficial to improving the dynamics and liquid retention of the battery.

[0092] Preferably, the parameters of the laser scribing process are: the distance between lines is 1-3 mm, and the depth of the lines is 5-30 μm; as an example, the distance between lines is 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, or within the range of any of the above values; the depth of the lines is 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or within the range of any of the above values.

[0093] Preferably, the spacing between the holes is 100-500 μm, and the depth of the holes is 5-30 μm. As an example, the spacing between the holes is 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 300 μm, 400 μm, 500 μm, or within the range of any of the above values; the depth of the holes is 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or within the range of any of the above values.

[0094] If the interval between laser scribing and drilling is too large, the improvement on the battery dynamics will be limited; if the interval between drilling and scribing is too close, the strain of the electrode material due to lithium insertion and extraction is large during the battery cycle, and too much internal space generated by drilling and scribing can easily lead to concentrated release of stress and strain of the electrode material, causing the battery to deform during the cycle. The effect of increasing energy density will be weakened and the risk of deformation during the cycle of lithium-ion batteries will be increased.

[0095] In the present application, the lithium-ion battery also includes a separator.

[0096] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.

[0097] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.

[0098] In some alternative embodiments, the mass percentage contents of the components in the positive electrode active material layer are as follows: 90-99.4 wt% of the positive electrode active material, 0.3-5 wt% of the conductive agent, and 0.3-5 wt% of the binder.

[0099] In some alternative embodiments, the mass percentage contents of the components in the negative electrode active material layer are as follows: 90-99.4 wt% of the negative electrode active material, 0.2-5 wt% of the conductive agent, and 0.4-5 wt% of the binder.

[0100] In some alternative embodiments, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, and metal powder.

[0101] In some alternative embodiments, the binder includes, but is not limited to, one or more of styrene-butadiene rubber latex, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, and carboxylated chitosan.

[0102] In some alternative embodiments, the negative electrode active material includes a carbon-based negative electrode material.

[0103] In some alternative embodiments, the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.

[0104] In some alternative embodiments, the negative electrode active material may further include a silicon-based negative electrode material.

[0105] For the battery according to the present invention, the silicon-based negative electrode material is selected from at least one of nano-silicon (Si), silicon oxide negative electrode material (SiO x (0 < x < 2)), and silicon-carbon negative electrode material.

[0106] In some alternative embodiments, the positive electrode active material is selected from one or more of transition metal lithium oxides, lithium iron phosphate, lithium manganese iron phosphate, lithium manganate, and lithium-rich manganese manganate; the chemical formula of the transition metal lithium oxide is Li 1+ x Ni y Co zM 1-y-z O2, wherein -0.5≤x≤0.5; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.

[0107] According to another aspect of the present application, there is provided an electric device, comprising the above-mentioned lithium-ion battery. The lithium-ion battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0108] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.

[0109] Example 1

[0110] This embodiment provides an electrolyte, and its specific composition and preparation method are as follows:

[0111] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), according to the total mass of the required electrolyte, ethylene carbonate (EC), fluoroethylene carbonate (FEC), and trifluoromethylethylene carbonate (TFPC) are mixed in a mass ratio of 2:3:2, and then 30% difluoroethyl acetate (Formula (II-1)) and 10% 2-fluoroisoxazole (Formula (I-2)) are added based on the total mass of the electrolyte and mixed evenly. Then, 12wt% of lithium hexafluorophosphate (LiPF6) and 8wt% of lithium bistrifluoromethylsulfonyl imide (LiTFSI) based on the total mass of the electrolyte are quickly added thereto, and after dissolution, 2.5wt% of 1,3-propane sultone (PS) and 2.5wt% of nitrile compounds (including HTCN and SN with a mass ratio of 1.5:1) are added based on the total mass of the electrolyte. After stirring evenly, the required electrolyte is obtained after passing the moisture and free acid tests.

[0112] Example 2-17

[0113] The difference between Example 2-17 and Example 1 is that the specific selection and dosage of the isoxazole compound and the fluorocarboxylate compound, A+B, B / A are different, as shown in the following table:

[0114] Table 1

[0115]

[0116] Examples 18-27

[0117] The difference between Examples 18-27 and Example 1 is that the specific selection and dosage of lithium salt, L / A, S%, and A / S are different, as shown in the following table:

[0118] Table 2

[0119]

[0120] Comparative Example 1

[0121] The difference between this comparative example and Example 1 is that no isoxazole compound is contained and the additive of difluoroethyl acetate is 40%.

[0122] Comparative Example 2

[0123] The difference between this comparative example and Example 1 is that the comparative example does not contain difluoroethyl acetate, a fluorinated carboxylic acid ester compound.

[0124] Comparative Example 3

[0125] The difference between this comparative example and Example 1 is that the addition amount of the isoxazole compound is 30%.

[0126] Comparative Example 4

[0127] The difference between this comparative example and Example 1 is that the added amount of the fluorocarboxylic acid ester compound difluoroethyl acetate is 50%.

[0128] Comparative Example 5

[0129] The difference between this comparative example and Example 1 is that an equal mass of N-ethyl-5-phenylisoxazole-3'-sulfonate is used to replace the isoxazole compound.

[0130] Comparative Example 6

[0131] The difference between this comparative example and Example 1 is that an equal mass of fluoroethylene carbonate is used to replace the fluorine-containing carboxylic acid compound difluoroethyl acetate.

[0132] Example E1

[0133] This embodiment provides a lithium ion battery, and its specific composition and preparation method are as follows:

[0134] 1) Preparation of positive electrode

[0135] The positive electrode active material is lithium cobalt oxide (LiCoO2, compaction density 4.2g / cm 3), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of the aluminum foil, with a single-sided coating thickness of 50 μm and a surface density of 15 mg / cm 2 The coated aluminum foil is dried, and then subjected to roller pressing, slitting, laser punching and other processes. The spacing between holes is 200 μm, and the depth of the holes is 30 μm to obtain the required positive electrode sheet. The porosity is tested to be 20%.

[0136] 2) Negative electrode preparation

[0137] The negative electrode active material artificial graphite (compression density 1.7g / cm 3 ), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 94.5:2.5:1.5:1:0.5, deionized water was added, and a negative electrode active slurry was obtained under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil, with a single-sided coating thickness of 60 μm and a surface density of 7 mg / cm 2 ; The coated copper foil was dried at room temperature, then transferred to an 80°C oven for drying for 10 hours, and then subjected to roller pressing, slitting, and laser scribing to form a recessed area with a width of 120 μm and a depth of 20 μm to obtain a negative electrode sheet with a porosity of 30% after testing.

[0138] 3) Preparation of electrolyte

[0139] The required electrolyte was prepared according to Example 1.

[0140] 4) Preparation of lithium-ion batteries

[0141] The positive electrode sheet, the negative electrode sheet and the commercial conventional separator (composed of a 5 μm thick polyethylene porous base film plus a 1 μm thick boehmite coating and a 1 μm thick polyvinylidene fluoride adhesive coating on both sides, the adhesive coating is located on the outermost side, and the total thickness of the separator is 9 microns) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; then, the battery cell is placed in an outer packaging aluminum foil, and after drying and passing, the electrolyte provided in Example 1 is injected into the outer packaging, and then after vacuum packaging, standing, formation, shaping, sorting and other processes, a square soft-pack lithium-ion battery is obtained, with a total capacity of 5000mAh, a thickness of 5.2mm, a width of 6.5cm, and a length of 8.0cm.

[0142] Examples E2-E7

[0143] The difference between Example E2-E7 and Example E1 is that the compaction density, porosity, and punching / scribing parameters of the negative electrode active material are different, as shown in the following table:

[0144] Table 3

[0145]

[0146] Examples E8-E33

[0147] The difference between Example E8-E33 and Example E1 is that the electrolytes of Example 2-Example 27 are used in sequence.

[0148] Comparative Examples E1-E6

[0149] The difference between Comparative Examples E1-E6 and Example E1 is that the electrolytes in Comparative Examples 1-6 are used in sequence.

[0150] Test Case

[0151] Test method for the porosity of active materials: gas replacement method is used for testing, and the specific method is as follows: after discharging the lithium-ion battery to 0% SOC, disassemble and remove the electrode, soak it in dimethyl carbonate (DMC) solvent for 12 hours, and then rinse it with DMC to remove the lithium salt attached to the electrode. After drying, use a slicer to cut the negative electrode into discs with a diameter of 12 mm, measure the thickness of 20 discs with a micrometer, calculate the volume of each disc separately and sum them to obtain the sum of the volumes of the 20 discs V1; then use a true density meter (such as JW-M100A fully automatic true density tester) to test the true volume V2 of the 20 discs, where the test gas is helium and the test environment temperature is 25±2°C; the porosity of the electrode is (V1-V2) / V1×100%.

[0152] The test method of the compaction density of the pole piece is as follows: Compaction density = surface density / (thickness of the pole piece after rolling - thickness of the current collector). The surface density is the mass of the material loaded on the unit current collector.

[0153] Battery performance test method:

[0154] (1) High temperature storage test of lithium-ion batteries:

[0155] Charge the lithium-ion battery to full capacity and place it in a thermostat at 85°C. Measure the thickness of the battery every 4 hours until the thickness of the battery expands by more than 15% of the initial thickness. The time it takes for the thickness to expand by more than 15% is taken as the storage life of the lithium-ion battery at 85°C.

[0156] (2) High temperature cycle performance test of lithium-ion batteries:

[0157] The voltage window of the lithium ion test is set to 3.0-4.5V. The battery is placed in a 45℃ constant temperature box, and the battery is charged to 4.25V at an initial rate of 3C, then charged to 4.5V at a rate of 1.5C, and then charged at a constant voltage until the current drops to 0.05C, and then discharged to 3.0V at a rate of 0.7C. This is one cycle. The maximum discharge capacity of the first three cycles is taken as the initial capacity of the battery, and the battery discharge capacity retention rate is measured. The number of cycles when the discharge capacity retention rate drops to 80% of the initial capacity is taken as the high temperature cycle life of the battery.

[0158] (3) Analysis of lithium-ion battery charging window:

[0159] The lithium-ion battery was charged at a constant current rate of 3C to an upper voltage limit of 4.5V, then charged at a constant voltage to full charge, and then discharged at a rate of 1C to 3.0V. This cycle was repeated 20 times, and the lithium-ion battery was disassembled in a fully charged state to observe the lithium deposition on the surface of the negative electrode.

[0160] (4) High voltage cycle stability test:

[0161] In a constant temperature box at 25°C, the lithium-ion battery was charged to 4.53V at a rate of 1C and discharged to 3V at a rate of 1C for 300 cycles, and the capacity retention rate of the lithium-ion battery was recorded.

[0162] (5) Wettability test: After the lithium-ion battery is filled with liquid, it is aged for 12 hours, and the lithium-ion battery is fully charged at a current of 0.2C. The battery interface is disassembled and observed. If the interface is golden and there are no black spots, purple spots or lithium deposition, it means that the wettability is good. If there are a small amount of black spots, purple spots or lithium deposition on the interface, it means that the wettability is poor. If there are a large number of purple spots, black spots or lithium deposition on the interface, it means that the wettability is very poor.

[0163] The specific test results are shown in the table below:

[0164] Table 4

[0165]

[0166]

[0167] As can be seen from the data in the above table, from Examples E1-E7, it can be seen that the reasonable regulation of the parameters of the depressed area, the compaction density and porosity of the negative electrode sheet can enable the lithium-ion battery to obtain better comprehensive performance. From Example E1 and Examples E8-E33, it can be seen that the reasonable adjustment of the content of each component in the lithium-ion electrolyte can enable the lithium-ion battery to have a better charging window (fast charging ability improvement), high temperature storage performance, high temperature cycle performance and high voltage stability. From Example E1 and Comparative Example E1, it can be seen that the electrolyte does not contain isoxazole compounds, resulting in poor dynamics of the electrolyte, thereby deteriorating the cycle performance and charging window, and the wettability of the electrolyte also deteriorates. From Example E1 and Comparative Example E2, it can be seen that the electrolyte does not contain fluorinated carboxylic acid esters, and the oxidation resistance deteriorates, thereby deteriorating the cycle performance and high temperature storage performance. From Example E1 and Comparative Example E3, it can be seen that the addition amount of isoxazole compounds is too high. Although the charging window of the electrolyte is good, the high voltage stability deteriorates, thereby deteriorating the cycle performance, and the high temperature full power storage performance also deteriorates. As can be seen from Example E1 and Comparative Example E4, the fluorocarboxylate content is too high. Although the high voltage stability is good, the repair ability of the SEI film during the cycle is deteriorated due to the relative decrease in carbonate solvents, so the high temperature cycle performance is deteriorated. As can be seen from Example E1 and Comparative Example E5, since the molecular weight of N-ethyl-5-phenylisoxazole-3'-sulfonic acid ester is too large, the dynamics deteriorate, thereby deteriorating the charging window and cycle performance of the lithium ion battery. As can be seen from Example E1 and Comparative Example E6, after using an equal mass of fluoroethylene carbonate to replace the fluorinated carboxylic acid compound, since the dynamics and stability of fluoroethylene carbonate are worse than those of fluorocarboxylate, the charging window, high temperature cycle and storage performance of the lithium ion battery are all deteriorated.

[0168] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. An electrolyte, characterized in that: include: The isoxazole compound and the fluorocarboxylate compound, based on the total mass of the electrolyte, the mass percentage A% of the isoxazole compound is 3%-20%, and the mass percentage B% of the fluorocarboxylate compound is 5%-40%.

2. The electrolyte according to claim 1, characterized in that The mass percentage A% of the isoxazole compound and the mass percentage B% of the fluorocarboxylic acid ester compound satisfy the following relationship: 15≤A+B≤50, and 0.5≤B / A≤10.

3. The electrolyte according to claim 1, characterized in that The isoxazole compound has the following structure: Wherein, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, alkyl, alkoxy, haloalkyl, haloalkoxy, alkylamino, and haloalkylamino; Preferably, R1, R2, and R3 are each independently selected from at least one of H, halogen, cyano, C1-C2 alkyl, C1-C2 alkoxy, C1-C2 haloalkyl, C1-C2 haloalkoxy, C1-C2 alkylamino, and C1-C2 haloalkylamino; Further preferably, the isoxazole compound has any of the following structures: More preferably, the isoxazole compound is a fluorine-containing isoxazole compound.

4. The electrolyte according to claim 1, characterized in that The fluorocarboxylic acid ester compound includes at least one of ethyl fluoroacetate, propyl fluoroacetate, methyl fluoropropionate, ethyl fluoropropionate, methyl fluoroacetate, propyl fluoropropionate, isopropyl fluoropropionate, isopropyl fluoroacetate, ethyl fluorobutyrate, ethyl fluoroisobutyrate, methyl fluoroisobutyrate, butyl fluoroacetate, isobutyl fluoroacetate and tert-butyl fluoroacetate; Preferably, the fluorocarboxylate compound has any of the following structures:

5. The electrolyte according to claim 1, characterized in that Also included are carbonate solvents; Preferably, based on the total mass of the electrolyte, the mass percentage of the carbonate solvent is 15%-45%.

6. The electrolyte according to claim 1, characterized in that Also included are lithium salts, including LiPF6 and sulfonic acid lithium salts; Preferably, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 8%-18%; the mass percentage of the sulfonic acid lithium salt is 3%-12%; Preferably, based on the total mass of the electrolyte, the total addition amount L% of the lithium salt is 16%-26%.

7. The electrolyte according to any one of claims 1 to 6, characterized in that Also included are sulfur-containing additives and / or nitrile compounds; Preferably, based on the total mass of the electrolyte, the mass percentage S% of the sulfur-containing additive is 1%-5%; Preferably, the mass percentage S% of the sulfur-containing additive and the mass percentage A% of the isoxazole compound satisfy the following relationship: 1≤A / S≤10; Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, vinyl bissulfate, methylene disulfonate, trimethylsilyl methane sulfonate, dimethyl methylene sulfonate, 4-acetylphenyl trifluoromethane sulfonate, phenyl trifluoromethane sulfonate, and 6-quinolyl trifluoromethane sulfonate; Preferably, the nitrile compound includes at least one of benzonitrile, p-toluene nitrile, 3,5-difluorobenzonitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, and 1,2,3-tris(2-cyano)propane.

8. A lithium ion battery, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 1 to 7.

9. The lithium-ion battery according to claim 8, characterized in that: The invention also includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, and the compaction density of the negative electrode active material is 1.65-1.80 g / cm 3 The porosity of the negative electrode sheet ranges from 10% to 45%.

10. The lithium ion battery according to claim 9, characterized in that: A recessed area is provided on the negative electrode active material layer, and the width of the recessed area is 50 μm-200 μm; Preferably, the depth of the recessed area is 3 μm-45 μm.

Citation Information

Patent Citations

  • Substituted isoxazoles for lithium batteries

    CN107636871A

  • Electrolyte additive as well as preparation method and application thereof

    CN116315085A

  • Battery

    CN118231779A

  • Lithium cell

    CN1484337A

  • Nonaqueous electrolyte battery

    JP2008218381A